Hukum dan Moralitas : Kajian Hubungan Asas Hukum dan Moral - Matondang, Togar Ibrahim; Lewoleba, Kayus K (Media Hukum Indonesia (MHI), 2024)
In this article we will discuss the relationship between legal principles and morality. Apart from that, it will also discuss how the principles of law and morality are related in several cases. The research method used in this research is a qualitative research method using legal literature and document analysis. The data collection technique used in this research is library research using secondary data sources in the form of law books, legal journals and legal articles. The type of research used is normative legal research, namely research carried out by analyzing and studying existing norms or applicable positive law, which are related to the problems discussed. Research results show that law and morals are two important pillars in the formation of a civilized society. While law provides a formal framework that helps maintain order and justice, morals provide ethical guidelines that help shape individual behavior in accordance with espoused social values. Both complement each other to create a harmonious and orderly environment, but it is important to remember that they work in different ways and have unique scopes. Respecting the law and practicing morality is the key to achieving a balanced and just social life.